Mathventure: numbers become an adventure! - Selvarajah, Thavarajah (2025)
Peperiksaan Semester Program Matrikulasi (PSPM) 23/24 examination report cite students perform poorly in Integration. To rectify the issue,students will be allowed to explore Integration using a historical story-mode setting whereby students amend their “timeline” on misconceptions, correct, and learn at their own pace using MathVenture. With game-setting mode, students are challenged to better themselves at Integration. Recurring issue of students demonstrating subpar analytical skills during Integration were identified, even with extensive guidance. This led to a target group of 14 students being selected and an intervention plan devised. The MathVenture product was utilized to create an engaging learning environment, fostering active student participation for these students. Digital tools like Quizizz were designed to assess student understanding and misconceptions. Data on students’ performance, including scores on Quizizz and formative test results were collected to measure the impact of MathVenture on students’ proficiency. Students’ emotions and feedback were reviewed through post-intervention discussion, obtaining qualitative insights on their experience. It was observed that 14 students who were given intervention using MathVenture displayed improved scores in formative-test1 displaying mastery of 80% score from 4 type of function given. Upon undergoing cycle 2, students displayed better scores in formative-test 2 of 90%. Qualitative feedback also indicated students enjoy more, remember steps better and could avoid misconception which was happening before the intervention. In line with 21st century learning skills, special activities such as gamification should be carried out to ensure better personal and meaningful learning.